A benchmark test case for swirling flows: design of the swirl apparatus, experimental data, and numerical challenges. Issue 7 (March 2019) - Susan-Resiga, R F; Popescu, C; Szakal, R; Muntean, S; Stuparu, A
Abstract: We introduce a new benchmark test case for assessing the robustness and accuracy of various numerical methodologies for simulating swirling flows in pipes and step diffusers. First we present the design and detailed geometry of the swirl generator and downstream test section. The swirl is generated with fixed plane blades, parallel to the symmetry axis, having a lean angle with respect to the meridian half-plane, in a mildly convergent pipe. The swirling flow is further ingested by a step diffuser with two cylindrical segments of 100 mm and 120 mm in diameter, respectively. This particular setup has a relatively simple geometry and it produces a swirl with pronounced axial deficit in the central region. Second, we present the methodology for axisymmetric swirling flow computation which account for the blades via blade body forces defined such as the flow tangency condition is enforced. Third, LDV measurements are presented in two survey sections corresponding to the two cylindrical pipe segments, and the accuracy of the numerical results is assessed. We conclude that this test case is suitable to define a new application challenge for assessing the ability of various numerical methodologies to accurately reproduce the turbulent swirling flows, with particular relevance for quasi-three-dimensional design and optimization of turbo-machines.